Silage Fermentation on Sweet Sorghum Whole Plant for Fen-Flavor Baijiu - Hongshen Li; Xinglin Han; Hongrui Liu; Jianqin Hao; Wei Jiang; Shizhong Li (Foods, 2021)
The technology for producing bioethanol from sweet sorghum stalks by solid-state fermentation has developed rapidly in recent years, and has many similarities with traditional Chinese liquor production. However, the product from sweet sorghum stalks was lacking in volatile flavors, and the level of harmful contents were uncertain, therefore it could not be sold as liquor. In this study, the protein, fat, and tannin in the clusters and leaves of sweet sorghum were utilized to increase the content of flavor compounds in the ethanol product through the anaerobic fermentation of Saccharomyces cerevisiae. Meanwhile, the silage fermentation method was used to extend the preservation time of the raw materials and to further enhance the flavors of Fen-flavor liquor, with ethyl acetate as the characteristic flavor. The effects of different feedstock groups on ethyl acetate, ethyl lactate, methanol, acetaldehyde, acetal, fusel oil, total acid, and total ester were evaluated by analyzing the chemical composition of different parts of sweet sorghum and determined by gas chromatograph. The effect of different fermentation periods on the volatile flavor of sweet sorghum Baijiu was evaluated. The yield of the characteristic volatile flavor was increased by the extension of the fermentation time. Sweet sorghum Baijiu with a high ester content can be used as a flavoring liquor, blended with liquor with a shorter fermentation period to prepare the finished Fen-flavor Baijiu, conforming to the Chinese national standard for sale.